Acute arthritis: predictive factors and current practice in the approach to diagnosis and management across two hospitals in Sydney. Issue 9 (4th September 2018) - Pavic, Katrina; Pandya, Jay; Sebak, Sophie; Shetty, Amith; Spencer, David; Manolios, Nicholas
Abstract: Background: Literature pertaining to the predictive factors for septic arthritis is limited. Aims: The primary objective was to investigate the predictive factors for septic arthritis. The secondary objectives were to investigate the predictive factors for crystal arthritis and to explore current practices in the management of acute arthritis. Methods: A retrospective analysis was undertaken. All patients with an acute arthritis who underwent a joint aspiration for diagnostic and management purposes were considered for inclusion. The outcome measures were patient demographics, findings on physical examination, findings on blood and synovial fluid analysis and management. Results: Of the patients who presented with an acute arthritis, 24 of the 172 joint aspirations undertaken were positive for bacteria (13.95%). Of the 172 joint aspirations, 90 were positive for crystals (52.33%). Investigated variables associated with increased risk for the presence of bacteria on synovial fluid included features of sepsis ( P < 0.001), joint‐restricted range of motion ( P = 0.048), elevated C‐reactive protein ( P < 0.001) and elevated total leukocyte count on synovial fluid ( P < 0.001). Of the 24 joint aspirations that were positive for bacteria, 13 had associated positive blood cultures (54.17%). Of the 172 joint aspirations, antibiotics were administered in 96 cases (55.81%). Of these, antibiotics were administered prior to joint aspiration in 41 cases (42.71%). Conclusions: In our study, the most common cause of acute arthritis was crystal arthropathy. An accurate physical examination in conjunction with synovial fluid analysis is of particular importance in diagnosing septic arthritis. Blood cultures are not a reliable substitute for joint aspiration but should nevertheless be undertaken.